2008
DOI: 10.1590/s0036-46652008000500003
|View full text |Cite
|
Sign up to set email alerts
|

Candida bloodstream infection: data from a teaching hospital in Mato Grosso do Sul, Brazil

Abstract: SUMMARYThe incidence of Candida bloodstream infection has increased over the past years. In the Center-West region of Brazil, data on candidemia are scarce. This paper reports a retrospective analysis of 96 cases of Candida bloodstream infection at a Brazilian tertiarycare teaching hospital in the state of Mato Grosso do Sul, from January 1998 to December 2006. Demographic, clinical and laboratory data were collected from medical records and from the hospital's laboratory database. Patients' ages ranged from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
11

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
2
17
0
11
Order By: Relevance
“…(14)(15)(16)(17)(18) Such results are similar to those found in this study, in which contamination with Candida parapsilosis following the cleaning/disinfection process persisted in three hospital mattresses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…(14)(15)(16)(17)(18) Such results are similar to those found in this study, in which contamination with Candida parapsilosis following the cleaning/disinfection process persisted in three hospital mattresses.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, Candida parapsilosis is usually spotted in the pediatric population, whereas the incidence of the Candida glabrata increases as age advances. (12,(14)(15)20) The Candida parapsilosis species is often found on the skin, and its transmission is predominantly exogenous, mainly by the hands of healthcare professionals. Its occurrence is also highly prevalent in children and premature newborns admitted in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…Furnaleto et al 12 observed that infections caused by Candida spp. were more frequent in older people (> 61 years), those less than one year old, and among ICU patients 19,20 .…”
Section: Discussionmentioning
confidence: 98%
“…However, Chang et al 19 reported a prevalence of C. albicans of 45.8% among analyzed candidemia infections at the University Hospital of the State of Mato Grosso do Sul. In Brazil and in our study, several studies have indicated C. tropicalis as the second most frequent isolate in cases of candidemia among hospitalized patients 12,20,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-albicans Candida species, such as Candida parapsilosis, have emerged as important infectious agents 35 . This pathogen can secrete glycosylated proteins that form biofi lms in solution and adhere to plastic materials such as intravascular catheters 36 .…”
Section: Discussionmentioning
confidence: 99%